Application of adult stem cells in obstetrics and gynecology: A scoping review - Andi Kurniadi; Muhammad Ary Zucha; Ardhanu Kusumanto; Siti Salima; Ali Budi Harsono (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: Advancements in regenerative medicine have led to the applicability of stem cell technology in various diseases. Stem cells that have self-renewable abilities may differentiate into several cell types to provide therapeutic potential. Among different stem cells, adult stem cells are considered as the safest with remarkable potential for therapeutic application. In this review, we provide current available evidence regarding the application of adult stem cells in medicine, especially in the field of obstetrics and gynecology. Objective: This scoping review aims to map and describe the current research on adult stem cell application in obstetrics and gynecology. Methods: We performed a systematic search on PubMed, Google Scholar, and Cochrane Library in August 2024 to identify research articles involving adult stem cells in the field of obstetrics and gynecology. We used the Deduplicate website to filter articles based on keywords that met our inclusion and exclusion criteria. The results were presented based on recommendations from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. Results: We found 42 articles that met the inclusion criteria. Some studies were clinical studies, whereas the majority were preclinical studies. We categorized the articles into clinical and preclinical studies to understand their applicability in human subjects. Conclusions: Adult stem cell therapy is a candidate treatment for several pathologies in obstetrics and gynecology. The promising results of adult stem cell therapy, especially in degenerative gynecologic diseases, may lead to further application of the technology in the near future.